Usage of Technology for Prisoner Distance Learners: Anadolu University OEF Case - Ugur Demiray, Sezen Unlu, Serap Sugur, Incila Cangoz, Esra Pınar Uca Gunes, (PJDOL, 2023)
Around the world, various correctional jurisdictions are struggling to enable the delivery of higher education into prisons. At a time when universities are moving increasingly online, very often access to the internet is restricted or disallowed in correctional environments. Three universities, all leading distance education providers in the countries in which they are based, are delivering higher education into prisons using technology to varying extents.